Perancangan sistem informasi akuntansi Penerimaan kas berbasis website - Purnamasari, Marlia; Maria Ulpah, Siti (Universitas Sains dan Teknologi Komputer, 2025)
Abstract. A store requires an effective and efficient accounting information system to manage its finances, ensuring business continuity and financial sustainability. One such case is Am Collection Store, which has not yet adopted computer technology. The store still uses manual methods for cash receipts processing. This Cash Receipt Application was designed using the waterfall method, applied as a system development method, and utilizes PHP and MySQL programming languages. The objective is for Am Collection Store to record all cash receipts from sales without the need for manual bookkeeping. The system design tools used include UML, such as Use Case Diagram, and Class Diagram. The result of this research is the design of a web-based accounting information system for cash receipts, which simplifies cash management to be more effective and efficient. Additionally, it produces detailed reports on matters related to the cash receipt processes from transactions conducted by both customers and sellers.